The nature of mathematics - Smith, Karl J. ([Place of publication not identifed] : Brooks/Cole Publishing Company, 2012)
This book was written for students who needs a mathematics course to satisfy the general university competency requirements in mathematics. Because of the university requirements, many students enrolling in a course that uses my book have postponed taking this course as long as possible .
The nature of mathematics /, The